2013
DOI: 10.1016/j.jacc.2013.05.089
|View full text |Cite
|
Sign up to set email alerts
|

Major Bleeding During HeartMate II Support

Abstract: The risk of bleeding peaks early after HMII implantation. Bleeding of thoracic and gastrointestinal sources dominates these events, although many patients undergo transfusions for anemia without an apparent source of hemolysis or bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 23 publications
0
58
2
1
Order By: Relevance
“…Another report found INR to be a poor predictor of bleeding when using the last INR measurement before a bleeding event. 23 Labile INR before implantation did not predict bleeding events in our analysis, although only 25% of patients were on warfarin before LVAD implantation. Thrombocytopenia was not assessed in our analysis.…”
Section: Discussionmentioning
confidence: 52%
“…Another report found INR to be a poor predictor of bleeding when using the last INR measurement before a bleeding event. 23 Labile INR before implantation did not predict bleeding events in our analysis, although only 25% of patients were on warfarin before LVAD implantation. Thrombocytopenia was not assessed in our analysis.…”
Section: Discussionmentioning
confidence: 52%
“…A recent study of 139 HMII patients showed the greatest risk of bleeding was within the first 2 weeks post-operatively and early bleeding was associated with decreased survival. 26 Later gastrointestinal bleeding is reported with rates as high as 13% in the ADVANCE: HVAD BTT Trial CAP. 14 A single-center study of 86 HMII patients reported gastrointestinal bleeding as a frequent source of morbidity for patients but not a factor that significantly impacts survival.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is again consistent with previous reports that cite bleeding as the most common perioperative event in these patients. 40 The 3rd leading cause of readmission was neurologic events, which occurred in 28 patients, or 13.3% of the LVAD-related admissions. Technological innovations designed to eliminate the driveline and to provide more biocompatible surfaces are clearly needed.…”
Section: Discussionmentioning
confidence: 99%